My book of manners: a lift the flap book - Hammonds, Heather (Hinkler Heatherton, Vic., 2007)
Follow the adventures of Emma, Carlos, Yasmin and Anthony as they discover how they can make friends with good manners. Kids will love the bright illustrations and fun stories as they lift the flaps to reveal how their behaviour affects others